1981
DOI: 10.1029/jc086ic01p00419
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison tests of moored current measurements in the upper ocean

Abstract: Mixed Layer Experiment (Mile) and the July-September 1978 Joint Air-Sea Interaction (Jasin) project, moored current measurements were made in the upper ocean with Savonius rotor and vane vector-averaging current meters (VACM), dual orthogonal propeller vector-measuring current meters (VMCM), and dual orthogonal acoustic travel-time vector-averaging current meters (ACM). Wind speeds and significant wave heights reached 20 m s -I and 5 m. The influence of mooring motion upon ACM, VACM, and VMCM measurements are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The accuracy of MCM data has been fairly well established and is expected to vary little from one deployment to another. Halpern et al [1981] found that at frequencies below 0.3 cph the amplitudes of velocity fluctuations recorded by a VACM suspended beneath a surface-following buoy were 5-15% larger than corresponding measurements made beneath a spar buoy or subsurface buoy. This result, obtained in the upper 100 m at mid-latitudes, is probably an upper bound for measurements within the EUC, where mean currents are strong and mooring motion is moderate.…”
mentioning
confidence: 69%
“…The accuracy of MCM data has been fairly well established and is expected to vary little from one deployment to another. Halpern et al [1981] found that at frequencies below 0.3 cph the amplitudes of velocity fluctuations recorded by a VACM suspended beneath a surface-following buoy were 5-15% larger than corresponding measurements made beneath a spar buoy or subsurface buoy. This result, obtained in the upper 100 m at mid-latitudes, is probably an upper bound for measurements within the EUC, where mean currents are strong and mooring motion is moderate.…”
mentioning
confidence: 69%
“…The offdiagonal horizontal Reynolds' stresses from two numerical experiments previously discussed by Schmitz and Holland [1982] are compared with observation in section 5, followed by summary and conclusions (section 6). Halpern et al [1981]. A general review of mooring design and performance may be found in Berteaux [1976].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve vector-averaging current meters (VACMs) were deployed in the array; seven VACMs were at a common depth of 10 m on surface moorings, and five VACMs were at 40 m and deeper levels on subsurface moorings. Current meter intercomparisons such as CMICE [Beardsley et al, 1981] and MILE [Halpern et al, 1981] indicate that the contamination of the 10-m current measurements by the wave-induced motion of the surface flotation is minimized by the slack surface mooring configuration and by the internal high-frequency vector averaging in the VACM: the expected experimental error in the 10-m current observations is less than 10%, especially during summer when the surface wave energy is at a minimum. A cross-sectional view of the array is shown in Figure 2 along with the numerical code used to refer to the instruments in the text and figures.…”
Section: The Moored Datamentioning
confidence: 99%